PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS TEORI VAN HIELE UNTUK MATERI LINGKARAN KELAS VIII SMP - Yulhelfina . (Jurnal Edukasi dan Penelitian Matematika, 2022)
Interactive learning multimedia is a supporting tool in the learning process that is able to activate students to learn with high motivation because of their interest in multimedia systems that present text, image, video, audio and animation displays so that they are more interesting and help visualize topics that are still abstract. The purpose of this research is to develop an interactive learning multimedia for material  of circles that was valid and practical. The type of research used is development research using the Plomp model which consists of a preliminary research stage and a prototype-making stage. The preliminary research phase includes needs analysis, student analysis, curriculum analysis and concept analysis. The prototype stage is the interactive learning multimedia design stage consisting of 1st prototype, 2nd prototype, 3rd prototype, and 4th prototype  which are evaluated using a formative evaluation design. The results of this study indicate that the interactive learning multimedia produced is valid and practical. Keywords – Geometry, Interactive learning multimedia, Plomp, Van hiele theory